Robust topology optimization of truss structures with random loading and material properties: A multiobjective perspective. (1st July 2015) - Richardson, James N.; Filomeno Coelho, Rajan; Adriaenssens, Sigrid
Highlights: Novel robust truss topology optimization with material and loading uncertainties. Spatially correlated material stiffness across truss included in problem formulation. Spectral stochastic finite element analysis, taking truss element length into account. Multiobjective approach to generate robust Pareto optimal solutions. Examples show effects of novel truss material modelling on the robust optimal designs. Abstract: In this paper an approach to robust topology optimization for truss structures with material and loading uncertainties, and discrete design variables, is investigated. Uncertainties on the loading, and spatially correlated material stiffness, are included in the problem formulation, taking truss element length into account. A more realistic random field representation of the material uncertainties is achieved, compared to classical scalar random variable approaches. A multiobjective approach is used to generate Pareto optimal solutions showing how the mean and standard deviation of the compliance can be considered as separate objectives, avoiding the need for an arbitrary combination factor.